Anthropometric study of emergency medical services providers (EMSP) in the United States. (September 2020) - Guan, Jinhua; Hsiao, Hongwei; Green, James D.; Whisler, Richard
Abstract: Introduction: Design of next-generation ambulance patient compartment requires up-to date anthropometric data of emergency medical service providers (EMSP). Currently, no such data exist in the U.S. A large-scale anthropometric study of EMSP in the U.S. were conducted. This report provided the summary statistics (means, standard deviation, and percentiles) of the study's results and examined the anthropometric differences between the EMSP dataset and the U.S. general population, and between the EMSP dataset and U.S. military personnel dataset, respectively. Method: An anthropometric study of 471 male and 161 female EMSP from across the continental US was conducted, using a sampling strategy that took into account age, sex, and race strata. Results: On average, male EMSP were found to be 18 mm taller and 7 kg heavier than US male general population, and 19 mm taller and 11 kg heavier than US male military personnel. Female EMSP were found to be 25 mm taller than US female general population, and 10 kg heavier than US female military personnel. Conclusions: These results showed that it would be inappropriate to apply general population or military data to the design of next-generation ambulance patient compartment. This new dataset provided the most recent and accurate EMSP anthropometric measurements available in the US. Practical Application: Data from this study provided an invaluable resource for the design of next-generation ambulances in the US.